IDENTIFICATION OF POTENTIAL ENTOMOPATHOGENIC FUNGI OF Tetranychus kanzawai Kishida (Tetranychidae: Acarina) USING ITS-5.8s rDNA REGION AS MOLECULAR MARKER - Sanjaya, Yayan; Ocampo, Virginia R.; Caoili, Barbara L. (AGRIVITA, Journal of Agricultural Science, 2016)
Fungi has been tested as one of the potential control agents for insect pests, which raises hopes for developing fungi as good biopesticides. The high variation within fungi species made taxonomic identification procedures more complex, thus molecular identification techniques are needed in addition to traditional morphological characteristics currently used as primary methods to classify fungi species. The objective of this research was to identify the species of the most pathogenic fungi to Tetranychus kanzawai Kishida using RAPD-PCR.  The internal transcribed spacer of 5.8s rDNA (ITS-5.8s rDNA) sequence of these fungal isolates were amplified using two sets of universal primers for ITS and then analyzed. Molecular identification showed that these  isolates had a higher  of similarity to Metarhizium anisopliae than Metarhizium flavoviride.